A New Formulation for Polymeric Separator Gels for Potential use in Blood Serum Separator Tubes. Issue 1 (February 2018) - Babakhani, Bahareh; Movahed, Saeed Ostad; Ghazy, Saghar; Ahmadpour, Ali
Blood serum separator tubes (SST) are used for collecting blood samples for performing clinical chemistry assays. Some SST's have separator gels inside the tube which enable them better separation of the blood serum from packed cells during centrifugation. The cost, weak performance and interaction with blood ingredients are the most concerns of the available commercial gels. A commercial and cheap silicone oil as a polymeric base of the gel was chosen and formulated without and with several fillers. Subsequently, the compounds were crosslinked through a free radical crosslinking mechanism using dicumyl peroxide (DCP). The crosslinking took place in both, an oven and as well as under microwave irradiation in normal and under pressure conditions. The FTIR spectrometer analysis showed that both chain ends of the used silicone oil were terminated with a vinyl group. It also revealed that blood serum separator gel can be produced from selected silicone oil type. Among of different curing apparatus, curing in an oven was preferred due to less curing time and electrical energy consumption. The curing in normal pressure showed better results when compared with curing under pressure. Increasing the filler and DCP with various amounts had positive effect on gel densities. Silica was the most efficient filler among of the studied fillers. The cured compound filled with 10 and 8 phr silica and DCP, respectively, was chosen as appropriate gel for SST due to suitable density and thixotropy. The selected gel was cured in oven under normal pressure for 30 minutes at 160°C.